Genome-wide analyses of alternative splicing in plants: Opportunities and challenges - Barbazuk, W. Brad; Fu, Yan; McGinnis, Karen M. (Genome Research, 2008)
Alternative splicing (AS) creates multiple mRNA transcripts from a single gene. While AS is known to contribute to gene regulation and proteome diversity in animals, the study of its importance in plants is in its early stages. However, recently available plant genome and transcript sequence data sets are enabling a global analysis of AS in many plant species. Results of genome analysis have revealed differences between animals and plants in the frequency of alternative splicing. The proportion of plant genes that have one or more alternative transcript isoforms is ∼20%, indicating that AS in plants is not rare, although this rate is approximately one-third of that observed in human. The majority of plant AS events have not been functionally characterized, but evidence suggests that AS participates in important plant functions, including stress response, and may impact domestication and trait selection. The increasing availability of plant genome sequence data will enable larger comparative analyses that will identify functionally important plant AS events based on their evolutionary conservation, determine the influence of genome duplication on the evolution of AS, and discover plant-specific cis-elements that regulate AS. This review summarizes recent analyses of AS in plants, discusses the importance of further analysis, and suggests directions for future efforts.
10.1101/gr.053678.106